Research on the Reform Path of Intelligent Manufacturing Practice Teaching under the Background of "New Four Modernizations" - Zhao, Houcheng; Li, Juan; Peng, Jianshe (International Journal of Social Sciences and Public Administration, 2025)
In the context of the "New Four Modernizations," intelligent manufacturing, as a key area driving the transformation and upgrading of the manufacturing industry, has made practical teaching reform crucial for enhancing the quality of talent cultivation. Based on an in-depth analysis of the current status of practical teaching in intelligent manufacturing, and considering the profound impact of the "New Four Modernizations," a systematic design of practical teaching reform paths has been developed. Under the background of electrification, practical teaching should emphasize content related to new energy technologies and green manufacturing; under the shared economy backdrop, there should be a focus on resource sharing and the cultivation of collaborative innovation capabilities; under the intelligentization backdrop, course content should include smart equipment, intelligent systems, and data analysis; under the networked backdrop, practical teaching should concentrate on improving network communication, information security, and system integration capabilities. By constructing the evaluation index system of practical teaching reform and using questionnaire survey, interview and data analysis to evaluate, the research found that the practical teaching after the reform has achieved significant improvement in curriculum system, training base construction, faculty quality and students’ practical ability. In addition, the research also put forward countermeasures and suggestions for the problems faced in the reform process, such as increasing the intensity of curriculum system update, increasing investment in practical training base construction, strengthening teacher training and broadening the channels for cultivating students’ practical ability, so as to provide practical guidance and theoretical support for the reform of intelligent manufacturing practice teaching.